Synaptic and Cellular Organization of Layer 1 of the Developing Rat Somatosensory Cortex - Shruti eMuralidhar; Yun eWang; Yun eWang; Henry eMarkram (Frontiers Media S.A., 2014)
We have performed a systematic and quantitative study of the neuronal and synaptic organisation of neocortical layer 1 in the somatosensory cortex in juvenile rats (P13 - P16) using multi-neuron patch-clamp and 3D morphology reconstructions. We used both subjective expert based and objective classification to establish distinct morphological groups. According to expert based subjective classification, the neurons were classified into six morphological types: (1) the dense axon neurogliaform cell (NGC-DA) and (2) a sparse axon neurogliaform cell (NGC-SA), (3) the horizontal axon cell (HAC) and (4) those with descending axonal colaterals (DAC), (5) the large axon cell (LAC) and (6) the small axon cell (SAC). We also used objective supervised and unsupervised analyses that confirmed 4 out of the 6 expert proposed groups, namely, DAC, HAC, LAC and a combined NGC. The cells were also classified into 5 electrophysiological types based on the Petilla convention; classical non-adapting (cNAC), burst non-adapting (bNAC), classical adapting (cAC), classical stuttering (cSTUT) and classical irregular spiking (cIR). The most common electrophysiological type was the cNAC type (40%) and the most commonly encountered morpho-electrical type of neuron was the NGC-DA - cNAC. Layer 1 cells are connected by GABAergic inhibitory synaptic connections with a 7.9% connection probability, as well gap junctions with 5.2% connection probability. Most synaptic connections were mediated by both GABAA and GABAB receptors (62.6%), as observed from the response characteristics to single pulse and train stimulations. A smaller fraction of synaptic connections were mediated exclusively by GABAA (15.4%) or GABAB (21.8%) receptors. Based on the morphological reconstructions, we found multi-synapse connections with an average of 9 putative synapses per connection. These putative touches were widely distributed with 39% on somata and 61% on dendrites.